EFL UNDERGRADUATE STUDENTS’ SUMMARIES: THE PRODUCT AND THE RESPONSE (RETAIN, 2020)
Students can do some ways to help them in the learning process in English class. One of them is summarizing from both lectures or books. This research focuses on the book summarization written by EFL students. Summarizing may help the students to comprehend the materials from the sourcebook.  Therefore, this research aimed to identify the type of summaries used by EFL undergraduate students and to describe their responses toward summary writing. This study was conducted in a university in Surabaya. The researcher used two instruments to collect the needed data which were the Type of Summaries rubric proposed by Horney (2009), and the second is focus group discussion. After getting the data, the results were analyzed qualitatively by occupying the three stages; familiarizing & organizing, coding & reducing, and interpreting & representing. The results showed that type of summaries used by the students were copy one sentence, copy multiple sentences, own words, and combination type. Moreover, it is also found that the students had difficulties in the process of summarizing. In conclusion, it is proven that students still plagiarized when summarizing from the source book and, they did not know how to summarize effectively. The implications of these findings are considered for academic individual to explore their students with summarizing and paraphrasing strategies.